Skinfold Thickness and Mid-upper Arm Circumference in Pediatric Patients with Chronic Kidney Disease - Suriadiredja, Siti Saqinah; Widiasta, Ahmdez; Rossanti, Rini (Majalah Kedokteran Bandung, 2025)
Chronic kidney disease (CKD) can impair the kidneys' capacity to manage nutrition, and any nutritional imbalances in CKD may affect the disease's progression. This study evaluated triceps skinfold (TSF) thickness and mid-upper arm circumference (MUAC) as indicators of nutritional status in children with early- and late-stage CKD at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. A descriptive cross-sectional design was used with secondary data from the nephrology division registry collected between August 2021 and August 2022. Data analysis was conducted with Microsoft Excel. The study involved 65 participants, with 32 in the early stage and 33 in the late stage. For early-stage patients, the average TSF was 13.75 mm and the MUAC was 12 cm, while, the average TSF an MUAC in the late stage were  11.39 mm and 11.70 cm, respectively. Based on TSF percentiles, most patients fell within the normal range, whereas MUAC measurements indicated that the majority were below normal. In terms of %TSF, most early-stage patients had above-average values, whereas late-stage patients were below average. All MUAC measurements indicated below-average values for both stages. Overall, TSF percentiles suggested that most patients had adequate nutritional status; however, %TSF revealed excess adiposity in early-stage patients and deficits in late-stage patients. MUAC consistently indicated deficits across both groups.